Pronunciation of 雨 (ame) and 飴 (ame) for Japanese Language Education Students Batch 2020 of Brawijaya University - Zalianti, Nur Halizah; Indrowaty, Sri Aju (Department of Languages and Literature, Faculty of Cultural Sciences, UGM, 2024)
This research discusses the pronunciation of ame/rain (雨) with high pitch (↗) to low pitch (↘) and ame/candy (飴) with low pitch (↘) to high pitch (↗) in Japanese Language Education Students Batch 2020. Based on the results of preliminary studies through Google Form, not all respondents were able to distinguish the pronunciation of ame/rain (雨) and ame/candy (飴). Therefore, this study aimed to determine the Japanese pronunciation of Japanese Language Education Students Batch 2020 of Brawijaya University by pronouncing one of the homophones namely ame/rain (雨) and ame/candy (飴). This research used a descriptive qualitative method. Based on simple random sampling technique, 10 respondents of Japanese Language Education Students Batch 2020 were selected as the data source of the research. The researcher examined students' understanding using voice recordings which were then analyzed through Praat to see the pronunciation results. The result of the research was on the word ame/rain (雨) 90% could pronounce it the correct tone. Then on the word ame/candy (飴) 50% could pronounce it the correct tone. 6 respondents made mistakes, this was due to learning strategies and second language culture. As a result of this study, the researcher suggested for analyzing the noun hoshii/want (欲しい) with hoshi/star (星) focusing on pitch, intensity, and respondents from the Department of Japanese Language Education and Japanese Literature who can be used as a comparison.